ARTIKEL PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII SMPTK IMANUEL TUAPAKAS - Kollo, Moses Kollo; Nubatonis, Kalfim (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to determine (1) the critical thinking abilities of Class VII students at SMPTK Tuapakas before implementing the problem based learning model; and (2) The process of implementing the problem based learning model in social studies learning to improve the critical thinking abilities of class VII students at SMPTK Imanuel Tuapakas. The research was located at SMPTK Imanuel Tuapakas, South Amanuban District, South Central Timor Regency. This research is Classroom Action Research (PTK). The data collection technique used was interviewing informants, namely teachers and students, and observing classroom activities. The results of this research are as follows: (1) The pre-test scores for Class VII SMPTK students are low, namely the students' classical learning completeness is 68.37%; (2) the results of applying the Problem Based Learning method in social studies learning were carried out through two cycles with the results of each cycle being in cycle I, after the post test was carried out there were 12 people or 44.44% of class VII students immediately fulfilled the KKM, namely getting a minimum score of 80 , while 15 people or 55.55 did not meet the KKM. Meanwhile, classical completeness in cycle I was 77.62%. Meanwhile, in cycle II, after the post test was carried out, of the 27 students who took the test, 23 people or 82.03% of students immediately met the KKM, and 4 people or 14.81 did not meet it.